2021
DOI: 10.1007/s10803-021-05002-y
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Gut Microbiota in Children with Autism

Abstract: Previous studies have reported dysbiosis in the gut microbiota (GM) of children with autism spectrum disorders (ASD), which may be a determining factor on child development through the microbiota-gut-brain axis. However, it is not clear if there is a specific group of dysbiotic bacteria in ASD. The aim of this study was to carry out a meta-analysis on the studies that analyze GM in children with ASD. 18 studies fulfilled our selection criteria. Our results showed a lower relative abundance of Streptococcus (SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 67 publications
(65 reference statements)
1
32
1
3
Order By: Relevance
“…The latest research in childhood neurodevelopmental disorders, including ASD, has transferred from genetics to environmental factors in the gut microbiome, which plays an important role [1,28,29]. Indeed, many studies have described the changes of intestinal microbiota of ASD children using non-culture-based methods [30][31][32]. This study investigated and compared the number, diversity, and community structure of gut bacteria from the fecal samples between healthy and ASD children using both the traditional plate counting method and 16S rRNA gene amplicon sequencing approaches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest research in childhood neurodevelopmental disorders, including ASD, has transferred from genetics to environmental factors in the gut microbiome, which plays an important role [1,28,29]. Indeed, many studies have described the changes of intestinal microbiota of ASD children using non-culture-based methods [30][31][32]. This study investigated and compared the number, diversity, and community structure of gut bacteria from the fecal samples between healthy and ASD children using both the traditional plate counting method and 16S rRNA gene amplicon sequencing approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed et al [43] found that there was no correlation between the severity of autism symptoms and the altered gut microbiome, although evidence of changes was revealed in the gut microbiome of autistic children compared to the unrelated control. However, Andreo-Martínez et al [32] recently found that it did not show evidence of a relevant gut microbiome-ASD association for Proteobacteria, Actinobacteria Firmicutes and Bacteroidetes phyla based on the meta-analysis integrated effect sizes of 18 previous studies to assess the potential association between gut microbiota and ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, eosinophilic esophagitis is associated with IgE-mediated food allergies which is associated with enteric microbiome alterations in non-ASD children [90,91]. As microbiome imbalances have been associated with ASD [92] and may have important consequences in immune regulation [93], microbiome alterations may be playing a role in immune dysregulation in ASD. The fact that chronic gastrointestinal symptoms have also been linked to non-IgE-mediated food allergies [94] and immune dysregulation [85] in children with ASD demonstrates the complex relationship between gastrointestinal symptoms and immune dysfunction in ASD and the complicated nature of management and treatment of ongoing symptoms in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in Section 2, the risks of bias of each study were measured following the model published in former studies [10]. Studies were considered to have a high (1-6), medium (7)(8)(9) or low (10-12) risk of bias in terms of the consolidated score out of 12. A low risk of bias was found in 14 articles selected in the present systematic review, and a moderate risk was found in 3 articles.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…In recent years, plenty of assays have demonstrated that enteric bacteria play a fundamental role in aspects of human health such as the promotion of adaptive immunity, cognition pathologies, inflammatory bowel disease (IBD), metabolic syndrome or colorectal cancer [2][3][4][5][6][7][8]. Even host emotions and behaviour have been associated with changes in the ecology of their GM [9,10]. In fact, the gut microbiome is currently considered as an independent organ that shows both physiological and pathological effects [11,12].…”
Section: Introductionmentioning
confidence: 99%